Fundamental VS Makro Ekonomi on Stock Price : Indonesian Stock Exchange (IDX) - Sarif, Reza; Sholihah, Mar’atus; Jaya, Tiara Juliana (PT FORMOSA CENDEKIA GLOBAL, 2024)
Geopolitical tensions especially those occurring in the Middle East, have significantly impacted the world economy. This impact was also felt by the Indonesian state, which impacted company share prices which experienced a decline due to geopolitical tensions, including the banking sector. Apart from geopolitical tensions, several other factors, such as the company's fundamental factors, also influenced the decline in share prices. Fundamental factors play an important role in determining a company's share price. These factors refer to various elements and variables that reflect the company's financial condition, operations, and prospects. So quite a few investors use fundamental analysis to assess whether current share prices reflect the company's true intrinsic value. This study seeks to reassess the elements affecting banking share prices by incorporating macroeconomic control variables related to these concerns to enhance the robustness of the findings. Utilizing a quantitative approach through panel data regression, the research focuses on banks listed on the Indonesia Stock Exchange from 2019 to 2023, with a sample of 16 companies meeting the selection criteria. The results reveal that Debt Equity Ratio (DER), Return On Assets (ROA), Return On Equity (ROE), GDP, inflation, and exchange rates collectively have a positive and significant impact on stock prices. However, when analyzed individually, only ROE and exchange rates show a significant effect, while DER, ROA, GDP, and inflation do not.